2021
DOI: 10.1021/acsapm.1c00474
|View full text |Cite
|
Sign up to set email alerts
|

Colorless Copolyimide Films Exhibiting Large Stokes-Shifted Photoluminescence Applicable for Spectral Conversion

Abstract: A series of semi-aliphatic polyimide (PI) copolymers (CoPIs) were prepared through the copolymerization of two dianhydrides, 1-hydroxy pyromellitic dianhydride (PHDA) and 4,4′-oxydiphthalic anhydride (ODPA), with 4,4′-diaminodicyclohexylmethane, in which the PHDA molar ratio was controlled at less than 5% to suppress aggregate formation in a solid state. Upon increasing the molar ratio of the PHDA unit, the fluorescence color of the CoPI films continuously changed from pink to yellow through an orange color ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…of H 2 SO 4 with variable r values, along with photographs under white light and UV irradiation. When a small amount of non-volatile H 2 SO 4 was added to the PAA (H 2 SO 4 -doped ODDC-TfA), the fluorescence at 440 nm was effectively suppressed [21], indicating that this fluorescence is attributable to the deprotonated anionic form, as shown in Figure S7. The E FRET of the H 2 SO 4 -doped ODDC-TfA increased by 9% with an increase in r from 1.98 to 7.92, which is higher than that of ODDC-TfA.…”
Section: Optical Properties Of Oddc-tfamentioning
confidence: 95%
See 3 more Smart Citations
“…of H 2 SO 4 with variable r values, along with photographs under white light and UV irradiation. When a small amount of non-volatile H 2 SO 4 was added to the PAA (H 2 SO 4 -doped ODDC-TfA), the fluorescence at 440 nm was effectively suppressed [21], indicating that this fluorescence is attributable to the deprotonated anionic form, as shown in Figure S7. The E FRET of the H 2 SO 4 -doped ODDC-TfA increased by 9% with an increase in r from 1.98 to 7.92, which is higher than that of ODDC-TfA.…”
Section: Optical Properties Of Oddc-tfamentioning
confidence: 95%
“…In our previous studies [21,45], we reported that ESIPT molecules are sensitive to the surrounding environment and may induce dissociation of the hydrogen atom in the amide group, generating an anionic form. The formation of anions in organic solvents was effectively suppressed with the addition of a small amount of TFA.…”
Section: Optical Properties Of Oddc-tfamentioning
confidence: 98%
See 2 more Smart Citations
“…Colorless and transparent polyimide (CPI) films have been well known for the excellent combined thermal and optical properties for many years in advanced optical and optoelectronic applications [ 1 , 2 , 3 ]. In many practical applications, CPI films have to be 1qconfronted with the long-term ultraviolet-visible (UV) light exposure, such as the fluorinated CPI thermal control films for the space aircrafts have to endure the large doses of ultraviolet (UV) and vacuum ultraviolet (VUV) irradiation during the servicing life, and the CPI substrates for flexible photovoltaic solar cells will be irradiated by sunlight in the whole life.…”
Section: Introductionmentioning
confidence: 99%